The Role of The Community in Recovery of The Children’s Psychic Post-Earthquake in Solok Selatan-Indonesia - Putri, Yeni; Chester, John Rey (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The purpose of this study is to express the role of the community in the psychological recovery of children after the earthquake in SouthSolok. The type of research used is descriptive qualitative research, with the sampling technique is purposive sampling. Data collection techniques used were interviews and documentation, then the data obtained were analyzed descriptively to present the facts encountered in the field. The results of the study are 1) The government's role in the psychological recovery of children after the earthquake in South Solok was very important where the government can reduce psychologists or volunteers who have the experience to help psychologically recover post-disaster children, 2) The role of NGOs in post-child psychological recovery earthquake disaster in SouthSolok Regency namely assisting experts in the process of psychological recovery of children after an earthquake, 3) The role of custom in the psychological recovery of children after the earthquake in south Solok Regency, 4) the role of universities in children's psychological recovery after the earthquake in SouthSolok Regency that is helping the government, NGOs and the community in psychological recovery of children by providing entertainment, such as reading stories, playing or watching together, and 5) the role of the community in the psychological recovery of children after the earthquake in South Solok Regency by sending assistance in the form of toys, clothes, foods and funds for these children. So, these five elements have a very important role and work together to be able to help the psychological recovery of children after the earthquake in south Solok.